Hambatan Dalam Proses Pembelajaran Tematik Muatan Ilmu Pengetahuan Alam di Kelas VB SDN 4 NagriKaler - Putri, Edis Eriansya; Pratama, Giar Anugrah; Supriatna, Supriatna; Muharam, Agus; Mustikaati, Wina (FKIP, PGSD, Universitas Slamet Riyadi, 2023)
Education is a benchmark for qualifying people. Education in Indonesia itself has undergone several changes, such as in 2006 when education in Indonesia used the KTSP curriculum, then in 2013 when education in Indonesia used the K13 curriculum, until in 2022 when the newest curriculum was passed, namely the independent curriculum. Natural science is one of the learning contents in the thematic 2013 curriculum. This study uses a quantitative description method. The subjects in this study were 25 students from class VB at SDN 4 Nagrikaler. The instruments we use are observation and learning achievement tests. The obstacles we encountered included infrastructure, teaching methods for educators, and students who were not yet fluent in reading. Then digital media is one solution to overcome these obstacles. The use of digital media is effective enough to improve student learning outcomes and is a solution to the barriers created by the ineffective use of conventional media. Keywords : obstacles, students, thematic, science content.